BIOCONVERSION OF MUNICIPAL ORGANIC WASTE USING BLACK SOLDIER FLY LARVAE INTO COMPOST AND LIQUID ORGANIC FERTILIZER - Abdul Kahar; Muhammad Busyairi; Sariyadi Sariyadi; Agus Hermanto; Ari Ristanti (Konversi, 2020)
Bioconversion of municipal organic waste using Black Soldier Fly larvae provides potential benefits. Apart from reducing municipal solid waste, BSF larvae (maggot) offer valuable added value as animal feed. The purpose of this study was to analyze the potential of BSF larvae in the bioconversion process of municipal organic waste, to analyze the quality of the compost produced and to analyze the nutrition content of BSF larvae (maggot). BSF eggs in hatching are covered with gauze which are given organic waste feed, then after hatching they become BSF larvae transferred to enlargement media. BSF larvae are fed leftovers that enter the TPST, so that the enlargement medium is wet. Feeding leftovers from TPST is done every day. The rearing time for BSF larvae is for one life cycle. Maggot harvesting is carried out at the age of the larva about 2-3 weeks. The final products of organic waste bioconversion are BSF larvae (maggot), compost and POC. It was found that the BSF larvae (maggot) could reduce organic waste (municipal organic waste) by 47.75%. Where the ability of BSF larvae (maggot) to consume municipal organic waste is 26,1508 g waste / g maggot. The protein, crude fat and ash content in maggots which were given organic waste were 41.8%, 14.63% 9.12%, respectively.